Nilai Tambah dan Profitabilitas Usaha Kerupuk Berbasis Udang pada Agroindustri Kayu Api Surya di Kecamatan Mendahara Kabupaten Tanjung Jabung Timur - Apriani, Kharisma; Zainuddin, Zainuddin; Kemala, Nida (Universitas Batangahari Jambi, 2025)
The Mendahara subdistrict in Tanjung Jabung Timur Regency has abundant fishery resources, especially shrimp caught by fishermen. For small businesses and home industries in the area, shrimp are processed into various food products to increase added value, as a profitable business, and to create local products. The purpose of this study was to describe the shrimp cracker business, analyze added value, and determine profit levels. The sampling method used was purposive sampling at one small industry that processes shrimp into crackers, namely Usaha Agroindustri Kayu Api Surya in Mendahara Ilir Subdistrict. The results of the study show that the average sales of Kayu Api Surya cracker business are Rp. 3,424,520 per production process with total variable costs of Rp 3,301,135 per production process, and total fixed costs of Rp.18,580 per production process, with an average of only 18 production processes per month. The added value is Rp. 8,495 per kilogram after deducting raw material costs of Rp. 20,000 per kilogram and other input costs of Rp.22,035 per kilogram. This shrimp chip business reaches a break-even point of 11.72 kilograms per production process and Rp. 515,785 per production process. The Marginal Income Ratio (MIR) of this business is 3.60 percent and the Margin of Safety (MOS) is 84.94 percent, with a profit margin of 3.06 percent. Profitability is too low, so it is recommended to improve variable cost efficiency, such as reducing shrimp waste from the production process, increasing labor productivity, and improving the efficiency of other materials such as vegetable oil and gas